Chemosensory characterization of Chardonnay and Pinot Noir base wines of Champagne. Two very different varieties for a common product. (15th September 2016) - Herrero, Paula; Sáenz-Navajas, Pilar; Culleré, Laura; Ferreira, Vicente; Chatin, Amelie; Chaperon, Vincent; Litoux-Desrues, François; Escudero, Ana
Highlights: Eighty-six volatiles quantified in Chardonnay and Pinot Noir Champagne base wines. Constitutive and discriminant aroma compounds were described in both sets. More constitutive compounds in Pinot Noir wines and more discriminant in Chardonnay. Sulfur compounds responsible for discriminant sensory terms in Champagne base wines. Fermentative compounds (aromatic buffer) at higher levels in Pinot Noir base wines. Abstract: Five different methodologies were applied for the quantitative analysis of 86 volatile molecules in 32 Chardonnay and 30 Pinot Noir Champagne white base wines. Sensory characterization was carried out by descriptive analysis. Pinot Noir wines had more constitutive compounds while Chardonnay wines had more discriminant compounds. Only four compounds predominated in Chardonnay wines: 4-vinylphenol, guaiacol, sotolon and 4-methyl-4-mercapto-2-pentanone. Correlation studies and PLSR models were calculated with sensory and chemical variables. For Pinot Noir wines, they were not as revealing as for Chardonnay base wines. Sulfur-related compounds were suggested to be involved in tropical fruit, dried fruit and citric sensory notes. This family of compounds seemed to be responsible for discriminant sensory terms in Champagne base wines. Fermentative compounds (aromatic buffer) were found at significantly higher levels in Pinot Noir wines, which would explain the fact that these wines were more difficult to describe in comparison with Chardonnay base wines.